Analyzing the overarching trends and developments of OTT platforms: A Bibliometric analysis (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study aims to examine the overall trends and development of the OTT Platforms that have emerged as the most accessed platforms for entertainment, leaving behind the television industry. OTT platforms have increasingly become a favorable source of entertainment. A total of 343 articles were retrieved from the Scopus database from 2008 to 2024, and then reduced to 272 documents (articles), after limiting to some keywords; a total of 270 articles were reviewed. A method for bibliometric analysis that employs cluster analysis and scientific mapping, utilizing the bibliographic coupling of documents. The study underscores the growth of Over-the-top platform services during the COVID-19 pandemic. With the help of bibliographic coupling, seven different clusters have been made and identified as Cluster 1 Transformative Impact of Streaming Media, Cluster 2 Evolution of Media Consumption, Cluster 3 User-Centric Revenue Models in the Entertainment Industry, Cluster 4 Media Investment and Streaming Dynamics, Cluster 5 Transformation in Television and Media Culture in the Digital Age, Cluster 6 Evolving Video Consumption and Delivery Models, Cluster 7 Impact of OTT Services on Telecom Industry. The research identified several elements that enhance the appeal of OTT platforms, including ease of access, cost-effectiveness, the ability to binge-watch, quality of service, personalization, and targeted offerings. This study adds to the current body of knowledge by examining new trends, developments, and areas that require further research.